The Role of ASEAN in Tackling the Main Issues of Transnational Crime in the Southeast Asia Region - Felix Ferdin Bakker; Andhika Parama Putra; Respati Triana Putri (Journal of Law and Border Protection, 2020)
Southeast Asia, a strategic region with a large border area, makes it an area prone to transnational crimes, especially terrorism, drug trafficking and human trafficking. This article aims to determine the role of ASEAN in tackling the main issues of transnational crime in the Southeast Asian region. International crimes in Southeast Asia are increasingly common. This research study uses normative legal research methods with qualitative data collection juxtaposed with descriptive analysis techniques so that the existing problems regarding transnational crimes, especially human smuggling, can be presented comprehensively and informatively. In dealing with this problem, ASEAN must play an active role by taking strategic steps through cooperating with other countries such as the United States and agreeing on various policies with ASEAN member countries related to handling transnational crimes, especially crimes of terrorism, drug trafficking and human trafficking.